2019
DOI: 10.31887/dcns.2019.21.3/gdom
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and addiction

Abstract: In this targeted review, we summarize current knowledge on substance-use disorder (SUD)-related cognitive deficits, the link between these deficits and clinical outcomes, and the cognitive training, remediation, and pharmacological approaches that have the potential to rescue cognition. We conclude that: (i) people with SUDs have moderate deficits in memory, attention, executive functions, and decision-making (including reward expectancy, valuation, and learning); (ii) deficits in higher-order executive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 94 publications
1
51
0
Order By: Relevance
“…Previous research identified deficits in executive function and decision-making ability as significant predictors of relapse of SUD ( 19 ). This study found that the iTBS modality produced therapeutic efficacy for the executive function of MUD patients, which might predict the therapeutic efficacy of iTBS for METH addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research identified deficits in executive function and decision-making ability as significant predictors of relapse of SUD ( 19 ). This study found that the iTBS modality produced therapeutic efficacy for the executive function of MUD patients, which might predict the therapeutic efficacy of iTBS for METH addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Executive function, as an important part of cognitive function, has gained increasing attention in studies on SUD, which has found that long-term drug abuse would cause widespread impairment of executive function ( 16 , 17 ). Lower executive function has been reported to be associated with relapse ( 18 ), and improving executive function reduces relapse and improves treatment outcomes for SUD ( 19 ). Executive function may therefore be an effective novel therapeutic target for improving drug addiction and relapse and a valid predictor of treatment efficacy for SUD.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that these cognitive control functions decrease in the course of addiction development while impulsive processes related to limbic structures increase in relevance [ 2 , 7 , 8 ]. Cognitive deficits in working memory, attention, inhibition, higher-order executive functions, and decision-making have been shown in individuals with substance-use disorders [ 9 , 10 ]. A growing body of research finds similar deficits in neurodegenerative disorders such as Parkinson’s disease [ 11 , 12 ] and in non-substance related disorders, including gambling disorder [ 13 , 14 ] and gaming disorder [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, impairments in the neuropsychological domain of "cognitive impulsivity" constitute one of the main features of substance users (2)(3)(4)(5), including chronic tobacco smokers (6)(7)(8). Particularly, impairments in cognitive impulsivity are considered relevant for the initiation and chronicity of substance use (5).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, impairments in cognitive impulsivity are considered relevant for the initiation and chronicity of substance use (5). Cognitive impulsivity is characterized by the cognitive subdomains of choice impulsivity (delay discounting) and risky decision making (2,4). Choice impulsivity refers to the tendency to opt for immediate pleasures/rewards (e.g., drug of abuse) over long-term gains (e.g., long-term health) (4), while "risky decision making" refers to a type of decisional process occurring when a an individual engages in decisions despite the risk of suffering known adverse consequences.…”
Section: Introductionmentioning
confidence: 99%